CAFÉ AS STUDENT’S INFORMAL LEARNING SPACE: A CASE STUDY IN BANDUNG, INDONESIA - Samuel Sri Kurnia Adityawirawan; Hanson E. Kusuma (DIMENSI (Journal of Architecture and Built Environment), 2021)
For the past years, the café's functionality has shifted from serving light food or beverages to being used by students as an informal learning space (ILS). This paper discusses university student's motivation to study in a café and the desired café's characteristics as an ILS in Bandung, Indonesia. The research uses a quantitative method using a questionnaire to reveal the dimensions of students' internal motivation and spatial characteristics of the café and its effect on students' informal learning responses while in the café. Results found 6 (six) groups of student motivations and 7 (seven) characteristics of cafés as an ILS. Results uncover a positive relationship between utilitarian motivation and physical characteristics in the form of the availability and quality of café amenities on students' cognitive and affective responses. It is implied that students choose a café as an ILS because such informal space can provide satisfactory physical amenities so that their learning performance is expected to increase. Through this trend, universities and/or related stakeholders could use this opportunity to improve the well-being of the student.